2022
DOI: 10.5194/acp-2022-261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: Atmospheric new particle formation in a coastal agricultural site explained with binPMF analysis of nitrate CI-APi-TOF spectra

Abstract: Abstract. The occurrence of new particle formation (NPF) events detected in a coastal agricultural site, at Qvidja, in Southwestern Finland, was investigated using the data measured with a nitrate ion-based chemical-ionization mass spectrometer (CI-APi-TOF). The binned positive matrix factorization method (binPMF) was applied to the measured spectra. It resulted in eight factors describing the time series of ambient gas and cluster composition at Qvidja during spring 2019. The most interesting factors related … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…We performed the analysis using the PMF Evaluation Tool (PET) v3.08 in Igor Pro 8. The details of applying positive matrix factorization (PMF) to aerosol mass spectrometry datasets have been discussed elsewhere (Paatero and Tapper, 1994;Paatero, 1999;. Prior to analysis before the PMF input matrix preparation, the variable values and errors of species mass concentrations and particle number concentrations were downweighted in reference to the highest average peak of the original organic mass spectrum, m/z 44 (f 44 ).…”
Section: Positive Matrix Factorization (Pmf)mentioning
confidence: 99%
See 1 more Smart Citation
“…We performed the analysis using the PMF Evaluation Tool (PET) v3.08 in Igor Pro 8. The details of applying positive matrix factorization (PMF) to aerosol mass spectrometry datasets have been discussed elsewhere (Paatero and Tapper, 1994;Paatero, 1999;. Prior to analysis before the PMF input matrix preparation, the variable values and errors of species mass concentrations and particle number concentrations were downweighted in reference to the highest average peak of the original organic mass spectrum, m/z 44 (f 44 ).…”
Section: Positive Matrix Factorization (Pmf)mentioning
confidence: 99%
“…Sulfuric acid (H 2 SO 4 ) is typically understood to be the most prevalent nucleation-inducing agent in NPF events, together with other airborne chemical species, including nitric acid (HNO 3 ), bases (e.g., amines), and organic acids (Zhang et al, 2012(Zhang et al, , 2015Kulmala et al, 2013;Wagner et al, 2017;Lehtipalo et al, 2018;Kürten, 2019;Lee et al, 2019;Brean et al, 2021;Olin et al, 2022). Numerous studies have also reported low-volatility organic species, such as terpene oxidation products and organic nitrates, participating in the formation of new particles (Berkemeier et al, 2016;Tröstl et al, 2016;Barsanti et al, 2017;Dall'Osto et al, 2018;Kerminen et al, 2018;Lee et al, 2019;Heinritzi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%